Slovak Republic : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Slovak Republic. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2016)
This 2015 Article IV Consultation highlights that Slovakia remains among Europe's stronger economies, with growth continuing to pick up in 2015, driven by strong domestic demand. A push to spend expiring European Union funds has underpinned rising investment while job creation and real wage growth have supported private consumption. Unemployment has fallen significantly since 2013, but is still about 11 percent overall, and is much higher for the long-term unemployed, youth, and women. The outlook is favorable with growth of 3-3.5 percent expected through the medium-term, reflecting sustained domestic demand as well as further contributions from the important export sector as substantial additional foreign auto sector investment is planned.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet